2009
DOI: 10.1128/jb.00504-09
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence ofAzotobacter vinelandii, an Obligate Aerobe Specialized To Support Diverse Anaerobic Metabolic Processes

Abstract: Azotobacter vinelandii is a soil bacterium related to the Pseudomonas genus that fixes nitrogen under aerobic conditions while simultaneously protecting nitrogenase from oxygen damage. In response to carbon availability, this organism undergoes a simple differentiation process to form cysts that are resistant to drought and other physical and chemical agents. Here we report the complete genome sequence of A. vinelandii DJ, which has a single circular genome of 5,365,318 bp. In order to reconcile an obligate ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
274
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 268 publications
(285 citation statements)
references
References 103 publications
(79 reference statements)
4
274
0
7
Order By: Relevance
“…P0AE08). Redundancy of protection mechanisms from oxidative damage seems to be a peculiarity of the aerobe A. vinelandii (Setubal et al, 2009), but, to our knowledge, studies devoted to investigate physiological responses to the generation of oxidative species in A. vinelandii are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…P0AE08). Redundancy of protection mechanisms from oxidative damage seems to be a peculiarity of the aerobe A. vinelandii (Setubal et al, 2009), but, to our knowledge, studies devoted to investigate physiological responses to the generation of oxidative species in A. vinelandii are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…AhpC is a member of the OxyR regulon, and in E. coli it was found that OxyR can respond to disulfide stress resulting from defects in the systems that maintain an intracellular reducing environment (Aslund et al, 1999). The genome sequence of A. vinelandii (Setubal et al, 2009) revealed the presence of an ahpC gene coding for alkyl hydroperoxide reductase (Uniprot acc. no.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations